Altered short chain fatty acid profiles induced by dietary fiber intervention regulate AMPK levels and intestinal homeostasis. Issue 11 (11th October 2019) - Li, Qian; Chen, Haixia; Zhang, Min; Wu, Tao; Liu, Rui
Abstract : Butanoate-mediated maintenance of intestinal integrity and homeostasis and the AMPK-dependent co-regulated pathway. Abstract : The objective of this study was to investigate the effects of dietary intervention on intestinal microbiota-mediated change in short chain fatty acid (SCFA) profile and intestinal homeostasis. Sequencing of the 16S rDNA of gut bacteria, metagenomics, intestinal epithelial transcriptomics, and metabonomics were conducted. Results showed that the dietary interventions altered the microbiota composition of cecal digesta, microbiota-mediated metabolism, and the gene expression profile in intestinal epithelial cells. Compared with red meat-diet-fed mice, fiber-diet-fed mice presented a shift in the gut microbiome toward increased production of butanoate, which was accompanied by up-regulation of microbiota- and AMP-activated protein kinase (AMPK)-dependent gene expression and decrease in serum concentrations of trimethylamine N -oxide (TMAO), triglyceride (TG) and glucose (GLU). The results suggested a new regulatory mechanism via which butanoate and AMPK activation contributed to intestinal integrity and homeostasis by affecting metabolism, intestinal barrier function and transporter expression.